2012
DOI: 10.1007/s10863-012-9479-3
|View full text |Cite
|
Sign up to set email alerts
|

A study of molecular changes relating to energy metabolism and cellular stress in people with Huntington’s disease: looking for biomarkers

Abstract: Huntington's disease (HD) is a neurodegenerative disorder characterized by a progressive motor and cognitive decline and the development of psychiatric symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…This delayed increase coincides with significant improvements in memory and learning achieved after longitudinal intervention. Our results are in accord with previous evidence demonstrating reduced BDNF/BDNF levels in Huntington's disease, in both humans and animal models [95][96][97][98][99][100] , and activity-dependent increases in BDNF expression in animals 77,82,104,105,109,110 and in human populations [106][107][108] . During the course of this investigation, however, a recent publication has questioned the utility of BDNF measurement as a biomarker for the monitoring of Huntington's disease 162 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This delayed increase coincides with significant improvements in memory and learning achieved after longitudinal intervention. Our results are in accord with previous evidence demonstrating reduced BDNF/BDNF levels in Huntington's disease, in both humans and animal models [95][96][97][98][99][100] , and activity-dependent increases in BDNF expression in animals 77,82,104,105,109,110 and in human populations [106][107][108] . During the course of this investigation, however, a recent publication has questioned the utility of BDNF measurement as a biomarker for the monitoring of Huntington's disease 162 .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports [95][96][97][98][99][100][101] , the ELISA results indicated lower levels of BDNF in the whole blood of Huntington's disease individuals, relative to normative data ( Figure 26). The assay to detect changes in mean BDNF concentration over the time period of the study revealed a non-significant reduction in mean BDNF levels after the control period (p=0.838) which worsened after one round of intervention (p=0.393).…”
Section: Bdnfsupporting
confidence: 91%
See 1 more Smart Citation
“…As was shown by Krzysztoń-Russjan et al, BCKDK (branched chain ketoacid dehydrogenase kinase) on the transcription level was increased in nuclear blood cells of HD subjects. 31 In turn, no significant abnormalities of KGDHC were also indicated in red blood cells and cultured fibroblasts of AD. 29 In this study the negative correlation noted between BCKDHC activity and thiamine concentration found in GM14467 cells is difficult to interpret, but it proves the cell specificity of energy metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…Our data indicated that the modification by TG2 impaired IP 3 R1-mediated cellular processes; therefore, we hypothesized that this regulation might lead to cellular dysregulation under pathological conditions. TG2 is up-regulated in the brain in HD model mice, including R6/2 and YAC128 mice (54)(55)(56)(57), and HD patients (49,(58)(59)(60)(61). Therefore, we tested whether IP 3 R was modified by TG2 in these HD models.…”
Section: Resultsmentioning
confidence: 99%